Make life simple: unleash the full power of the parallel tempering algorithm - Bittner, Elmar; Nuβbaumer, Andreas; Janke, Wolfhard (Physical review letters, 2008)
We introduce a new update scheme to systematically improve the efficiency of parallel tempering simulations. We show that, by adapting the number of sweeps between replica exchanges to the canonical autocorrelation time, the average round-trip time of a replica in temperature space can be significantly decreased. The temperatures are not dynamically adjusted as in previous attempts but chosen to yield a 50% exchange rate of adjacent replicas. We illustrate the new algorithm with results for the Ising model in two and the Edwards-Anderson Ising spin glass in three dimensions.
Gesehen am 13.11.2017